Microfluidic Bead Suspension Hopper - Price, Alexander K. (American Chemical Society, 2014)
[Image: see text] Many high-throughput analytical platforms, from next-generation DNA sequencing to drug discovery, rely on beads as carriers of molecular diversity. Microfluidic systems are ideally suited to handle and analyze such bead libraries with high precision and at minute volume scales; however, the challenge of introducing bead suspensions into devices before they sediment usually confounds microfluidic handling and analysis. We developed a bead suspension hopper that exploits sedimentation to load beads into a microfluidic droplet generator. A suspension hopper continuously delivered synthesis resin beads (17 μm diameter, 112,000 over 2.67 h) functionalized with a photolabile linker and pepstatin A into picoliter-scale droplets of an HIV-1 protease activity assay to model ultraminiaturized compound screening. Likewise, trypsinogen template DNA-coated magnetic beads (2.8 μm diameter, 176,000 over 5.5 h) were loaded into droplets of an in vitro transcription/translation system to model a protein evolution experiment. The suspension hopper should effectively remove any barriers to using suspensions as sample inputs, paving the way for microfluidic automation to replace robotic library distribution.